2015
DOI: 10.1073/pnas.1507300112
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of a mutational hot spot to hemoglobin adaptation in high-altitude Andean house wrens

Abstract: A key question in evolutionary genetics is why certain mutations or certain types of mutation make disproportionate contributions to adaptive phenotypic evolution. In principle, the preferential fixation of particular mutations could stem directly from variation in the underlying rate of mutation to function-altering alleles. However, the influence of mutation bias on the genetic architecture of phenotypic evolution is difficult to evaluate because data on rates of mutation to function-altering alleles are sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
97
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 94 publications
(111 citation statements)
references
References 66 publications
(73 reference statements)
11
97
0
3
Order By: Relevance
“…Surely there are other ways to adapt, and other ways to adapt by increasing affinity, given that previous studies (cited by Galen et al) found other hemoglobin mutations that increase affinity in high-altitude species; indeed, the authors themselves discovered a different affinity-increasing mutant at a low frequency in house wrens (see figure 4 in ref. 1). We see the Val-to-Ile change, not because it is the fittest alternative, but because it is so strongly favored by the "arrival of the fittest."…”
mentioning
confidence: 94%
See 3 more Smart Citations
“…Surely there are other ways to adapt, and other ways to adapt by increasing affinity, given that previous studies (cited by Galen et al) found other hemoglobin mutations that increase affinity in high-altitude species; indeed, the authors themselves discovered a different affinity-increasing mutant at a low frequency in house wrens (see figure 4 in ref. 1). We see the Val-to-Ile change, not because it is the fittest alternative, but because it is so strongly favored by the "arrival of the fittest."…”
mentioning
confidence: 94%
“…This influence is typically attributed to neutral evolution, presuming that mutation is a weak force easily overcome by selection, so that any noticeable effect of mutation must signal a lack of selection. However, in PNAS Galen et al (1) propose a case of mutation-biased adaptation, in which the course of evolution reflects both a bias in mutation and a fitness benefit. How important are mutational biases in shaping adaptation?…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, estimates of gene flow between lowland and highland populations of Crested Ducks ( Lophonetta specularioides ) obtained based on hemoglobin alleles are much lower than those inferred from neutral markers; in light of biochemical properties of amino acid substitutions differing across elevations, such differences in hemoglobin gene flow are consistent with a role for selection structuring genetic and phenotypic variation (Bulgarella et al., 2012). Likewise, hemoglobin variants with increased affinity for oxygen occur at a greater frequency in high‐elevation populations of House Wrens ( Troglodytes aedon ) relative to those from lowland areas, and F st across elevations for a functionally important site in the βA‐globin gene is greater than F st values for most coding SNPs across the genome (Galen et al., 2015). Because the high‐elevation βA‐globin genotype is derived, colonization of high‐elevation environments by House Wrens presumably involved adaptive evolution in protein function.…”
Section: Introductionmentioning
confidence: 99%